Learning to work together: conceptualizing doctoral supervision as a critical friendship. Issue 1 (2nd January 2020) - Richards, K. Andrew R.; Fletcher, Tim
ABSTRACT: Faculty supervision has been identified as a critical component of doctoral student socialization in both the higher education and physical education literature. Nevertheless, few faculty members receive explicit training for supervisory roles, and few published scholarly articles discuss the process through which faculty members develop supervisory practices. Drawing from occupational socialization theory, and adopting self-study of teacher education practices as a methodology, the current study sought to understand how Kevin, a faculty member in physical education, developed, articulated, and enacted what it meant to be a student-centered doctoral supervisor while navigating the power dynamics involved in supervision. Kevin was in his second year in a tenure-track faculty position at the beginning of the study, and was in the process of taking on additional roles related to doctoral supervision. Tim, a faculty member at a different university with experience supervising doctoral students, served as Kevin's critical friend. The dataset included Kevin's reflective journal and critical friend conversations with Tim, which were analyzed in reference to key turning points. Kevin came to frame doctoral education as a form of critical friendship, which he defined as including three key elements: (a) finding a balance when supporting students, (b) maintaining social relationships with students, and (c) giving up control and allowing students to struggle. The results of this study highlight the difficulties and benefits of critically examining one's own practice in the context of doctoral supervision and provide recommendations for others who engage in supervisory roles.